Factors associated with reduced functional capacity in the elderly of a nursing home at Curitiba, PR (Research, Society and Development, 2023)
This study aims to analyze the variables associated with the reduction of functional capacity among residents of a nursing home in the city of Curitiba, Brazil. A retrospective cohort study was conducted, analyzing the sociodemographic and clinical-functional characteristics of individuals upon admission and during the institutionalization period of older adults who resided in a nursing home between July 2010 and July 2020. The final sample consisted of 114 participants, of whom 79.8% (n=91) had functional assessment using the Katz Scale upon admission, with functional decline identified during the institutionalization period in 44.4% (n=24) of the previously independent individuals and in 25% (n=8) of the partially dependent individuals. The use of sedative psychotropic medications, medications with anticholinergic action, both at admission and during institutionalization, and the development of cerebrovascular disease were significantly associated with functional decline. The results of this study demonstrate factors that may be related to functional decline in the institutionalized elderly population, which are of interest for clinical practice in the care of vulnerable older adults at risk of functional capacity loss. There was a scarcity of similar national data, highlighting the importance of conducting similar studies in other Brazilian nursing homes to verify the replication of these results.